Penguatan Kelembagaan dan Tata Kelola Pemerintahan dalam Pelindungan Hak Asasi Manusia Pekerja Migran Indonesia di Era Globalisasi - Edi Pranoto; Eva Arief; Muawafah (Fakultas Hukum Universitas Islam Indonesia, 2025)
Globalization has increased cross-border labor mobility, positioning Indonesian migrant workers (PMI) as key actors in the international economy. Although Indonesia has established progressive regulations through Law No. 18 of 2017 and Law No. 6 of 2023, the protection of PMI’s human rights still faces challenges, such as weak coordination between central and regional authorities, suboptimal integration of national data systems, and limited diplomatic capacity in addressing rights violations in destination countries. This study aims to analyze institutional strengthening and governmental governance reforms to enhance the protection of PMI’s human rights. The research questions are: (1) how institutional strengthening can improve the protection of Indonesian migrant workers’ human rights, and (2) how governance reforms can address challenges in protecting the human rights of Indonesian migrant workers. The study employs a normative juridical method with a descriptive-analytical approach. Data were sourced from national legal documents, reports from KP2MI, the Ministry of Foreign Affairs, and the National Human Rights Commission, as well as literature reviews and cases of PMI human rights violations from 2018–2025. The results indicate that institutional strengthening requires restructuring inter-agency authorities, integrating national data systems, and implementing progressive human rights diplomacy with destination countries. Governance reforms must include inter-agency coordination, human rights-based public services, and enhanced capacities of regional governments and complaint-handling institutions. This holistic approach is essential to ensure the effective protection of PMI’s rights, adaptiveness to global dynamics, and compliance with both national and international standards.